2019
DOI: 10.20473/pmnj.v5i1.12483
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Perawat dalam Manajemen Nyeri Non Farmakologi pada Neonatus Pendekatan Theory of Planned Behavior (TPB)

Abstract: Introduction: Pain in the neonate may result in negative behavior, physiology and metabolic responses. This study aims to analyze the behavior of nurses in the implementation of non-pharmacological pain management in neonates who performed minor invasive action with the approach of Theory of Planned Behavior (TPB).Methods: This research was a descriptive study of analysis with research design cross sectional. The population of this study were nurses working in the neonatal ward and neonatal intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…nonpharmacological. While the results from Trihastutik et al in 2019 showed that nurses' knowledge in pain management was 9.1% less, 67.3% moderate, 23.6% good, and the behavior or attitude of nurses in pain management was 29.1% positive, 70.9% negative attitude [4]. Based on the results of observations during the practicum at Rumah Sakit Islam A. Yani, the phenomena that occur in the children's room are still very less effective.…”
Section: Introductionmentioning
confidence: 99%
“…nonpharmacological. While the results from Trihastutik et al in 2019 showed that nurses' knowledge in pain management was 9.1% less, 67.3% moderate, 23.6% good, and the behavior or attitude of nurses in pain management was 29.1% positive, 70.9% negative attitude [4]. Based on the results of observations during the practicum at Rumah Sakit Islam A. Yani, the phenomena that occur in the children's room are still very less effective.…”
Section: Introductionmentioning
confidence: 99%